Leadership in Action : Issues and Observations - Making the Connection Between Art and Leadership - Asbjörnson, Kevin (Center for Creative Leadership, 2007)
Performing artists and leaders face very similar challenges and expectations. They have a great deal in common and a great deal to learn from each other.